DIGITAL AEROTRIAINGULATION (Journal of Engineering, 2004)
One of the major advantages of digital photogrammetry is the potential to automate productionprocesses efficiently , thus substantially improving the price \ performance ratio for photograrnmetric products. The other major advantage of digital photogrammetry is increasing the accuracy of the final output results .Image processing and computer vision techniques have suc,pessfully been employed for facilitating automated procedures in digital aerial images such as interior orientation , relative orientation , point transfer in photogrammetric block triangulation , and the generation of DTM S .Digitat a.erotriangulation including image import and image minification , interior orientation , point transfer , control point measurements , bundle block adjustment , '*'hich is one of the most complex process$s in